Scott, Contempt And Pity - Social Policy And The Image Of The Damaged Black Psyche, 1880-1996 - Davis, Dernoral (Teaching History: A Journal of Methods, 1999)
Societal-generated images and perceptions of a population group invariably exact a price. Even when such images are the handiwork of scholars and experts, a toll results nonetheless, often with social and public policy implications. African-Americans are arguably the most glaring population group example of this scenario. Certainly the scholarly debate continues regarding the historical origins of popular perceptions of and about African-Americans. There is as well an ongoing scholarly debate about the social and public policy ramifications of popular images of African-Americans, both historical and contemporary. In his recent publication, Contempt and Pity: Social Policy and the Image of the Damaged Black Psyche, 1880-1996, Daryl Scott of Columbia University endeavors to isolate and identify specific bodies of social science scholarship that have given historical currency to notions of pathology in Black life. Indeed, as to his own scholarly intent, Scott leaves little, if any, doubt. It is "to make a contribution to the study of social science history by combining a study of social science ideas with the making of social policy." Scott provides an engagingly crafted analysis and discussion of the linkage between social science scholarship, Black imagery, and social policy engineering.